A 67-year-old Female with Malignant Splenic Non-Hodgkin Lymphoma at Banten Regional General Hospital: A Case Report - Rastono, Adi; Archie, Avicenna Muhammad (Media Publikasi Cendekia Indonesia, 2024)
Non-Hodgkin's lymphoma (NHL) is a type of lymphoproliferative disorder primarily involving lymph nodes but can extend to extranodal sites like the spleen. When NHL originates in the spleen, it is classified as primary splenic NHL. Due to its unusual presentation, it may resemble other splenic conditions in clinical appearance. In this Journal we report a rare case of splenic lymphoma in a 67-year-old female with symptoms of abdominal pain in the left quadrant of the abdomen. Multislice Computerized Tomography (MSCT) scan of the abdomen to axial pelvis section showed splenomegaly with solid mass et causa suspect splenic lymphoma. The diagnosis of malignant splenic non-Hodgkin lymphoma can be made after splenectomy and histopathology examination which is consistent with clinical and radiologic examination found in the Patient.